Engineering a bivalent nanoparticle vaccine with PCV2 capsid protein and PRRSV epitopes - Jun Ma; Xun Xiao; Yanrong Zhou; Wen Huang; Jie Sun; Xinjian Chang; Shaobo Xiao; Liurong Fang (Journal of Nanobiotechnology)
Abstract Background Coinfection with multiple viruses is a common occurrence in the pig industry. Porcine reproductive and respiratory syndrome virus (PRRSV) and porcine circovirus type 2 (PCV2) are two significant pathogens, with a notable prevalence of their coinfection observed in clinical settings. However, reports on corresponding combination vaccines against PRRSV and PCV2 are scarce. The capsid (Cap) protein encoded by PCV2 is highly immunogenic, and recombinant Cap expressed in vitro can self-assemble into virus-like particles (VLPs), providing a promising strategy for developing bivalent vaccines against both PRRSV and PCV2. Method Three novel nanoparticle vaccines (Cap-DS, Cap-DP, and Cap-DE) were engineered by inserting multiple neutralizing epitopes from PRRSV (GP5B epitope, GP3I epitope, and GP5IV epitope) into the PCV2 Cap protein. These recombinant proteins, produced using a baculovirus expression system, successfully formed VLPs in vitro. Results Immunization of BALB/c mice with these nanoparticle vaccines significantly enhanced T-lymphocyte immune responses and elicited high-titer antibodies against both PCV2 and PRRSV. Notably, Cap-DS induced more potent serum neutralizing antibodies against PRRSV compared to Cap-DP and Cap-DE. Piglets immunized with Cap-DS, upon challenge with PRRSV, demonstrated significant protection compared to the PBS-immunized control group. Conclusions These findings indicate that Cap-DS is a promising candidate for the development of a bivalent nanoparticle vaccine against PRRSV and PCV2 infections, addressing a significant gap in current swine vaccination strategies. Graphical Abstract